PENGARUH PEMBERIAN THE EUPHORBIA MILII DAN PROPOLIS TERHADAP GAMBARAN HISTOLOGIS GINJAL TIKUS WISTAR JANTAN - Wicaksana, I Dewa Agung Gede Oka Dwi; Linawati, Ni Made; Arijana, IGK Nyoman; Ratnayanti, I Gusti Ayu Dewi (E-Jurnal Medika Udayana, 2022)
ABSTRACT Introduction: There are various kinds of traditional medicine in Indonesia, either derived from animals or from plants. One of kind traditional medicine that can be found in Indonesia are Euphorbia milii and propolis which has benefits as an immunomodulator and as an antioxidant. The use of traditional medicine with uncertain doses and time intervals may cause some adverse effects. The main purpose of the study is to know the effect of tea which made from Euphorbia milii and propolis on the histological appearance of the kidney of male wistar rats. Methods: This study used a randomized post test only controlled group. There are 4 groups of rats were taken from total 24 male wistar rats with an age range 2-3 months and a bodyweight ± 200 grams. The controlled group (K) was given aquabidest, the intervention group (P1-P3) was given the tea of Euphorbia milii and propolis, then terminated and continued with histological examination by measuring the diameter of the glomerulus. Data analysis technique is One Way Anova and Post Hoc with LSD test. Result: Based on the result of data analysis, the difference between the controlled group (K) and the intervention group (P1-P3) was not significant. Conclusion: Based on the result, the conclusion is that the tea of Euphorbia milii and propolis did not cause significant damage to the kidneys of male wistar rats. Keywords : Euphorbia milii, propolis, glomerulal diameter